Interdependence of Urban Environmental Degradation on Community Mental Health Disorders - Riza, Risa Bernadip; Yakobus, I Ketut; Ardiansyah, Ardiansyah; Ruagadi, Henry A.; Nursinah, Nursinah (International Journal of Health Sciences, 2025)
This research examines the relationship between urban environmental degradation and community mental health disorders, focusing on the interdependence between the two. Environmental degradation, which includes air pollution, decreasing quality of green spaces, and increasing deterioration of city infrastructure, has been shown to contribute to a decline in the quality of life in urban environments. The impact on people's mental health, such as anxiety, stress, and depression, becomes more significant as environmental conditions worsen. Air quality degradation and lack of open space often affect psychological well-being, increase levels of discomfort, and worsen mental health conditions, especially among people living in more vulnerable areas. This research methodology uses a quantitative approach with a cross-sectional and longitudinal design to analyze the relationship between environmental degradation and mental health. The sampling technique used was stratified random sampling, where the population was divided based on the level of environmental degradation (high, medium, low) in major cities in South Sulawesi. The sample included approximately 500 respondents for the cross-sectional design and 200 respondents for the longitudinal design. Mental health was measured using standardized psychological questionnaires to evaluate levels of anxiety, stress, and depression, while environmental conditions were measured using parameters of air pollution, quality of green open spaces, and infrastructure degradation. The findings suggest that integrated environmental improvements, such as green open space management and pollution control, can improve the physical and psychological conditions of urban residents. This study recommends the design of more environmentally friendly urban policies to improve the quality of life and psychological well-being of city residents.